If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 2(q + 25) Reorder the terms: 90 = 2(25 + q) 90 = (25 * 2 + q * 2) 90 = (50 + 2q) Solving 90 = 50 + 2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2q' to each side of the equation. 90 + -2q = 50 + 2q + -2q Combine like terms: 2q + -2q = 0 90 + -2q = 50 + 0 90 + -2q = 50 Add '-90' to each side of the equation. 90 + -90 + -2q = 50 + -90 Combine like terms: 90 + -90 = 0 0 + -2q = 50 + -90 -2q = 50 + -90 Combine like terms: 50 + -90 = -40 -2q = -40 Divide each side by '-2'. q = 20 Simplifying q = 20
| Z=.5a-.5b(6-.2z) | | 3h+1=13 | | 10x-2y=11 | | 2(u-9)-9=-6(-2u+7)-u | | r+10=-9r-10 | | -9y+1=-y+25 | | -5y=-7y-8 | | y-25=9y-1 | | 13z-15z-4=0 | | 10q=9q-4 | | 60-12x=9-6x | | p=15-3Q | | 6x-9y-7y+11x+8= | | -2(2t+4)=20 | | 4X+X-20=180 | | -4j+9=7j+9 | | 2x+3(32.5-0.5x)=105 | | 3^x=1/81 | | 7*x^2-x^1/3 | | -t=-9-t | | 8v+48=2(v-6) | | 1/3=x/3(3/5) | | 5*a+3*b+10=147 | | 7/3×p/3 | | 4-9f=-4-9f | | 2(11+-1y)+2(0)=22 | | 5/8=x/(1/7) | | 3(y+3)=7y-7 | | 3(11+-1y)+3y=33 | | -7(4a+9)=14a | | abs(z+4-2i)=abs(z-8+2i) | | 2/5(m)14 |